A Product Market Theory of Worker Training - Hans Gersbach; Armin Schutzler (Institute for the Study of Labor (IZA), 2001)
We develop a product market theory that explains why firms invest in general training of their workers. We consider a model where firms first decide whether to invest in general human capital, then make wage offers for each others? trained employees and finally engage in imperfect product market competition. Equilibria with and without training, and multiple equilibria can emerge. If competition is sufficiently soft and trained workers are substitutes, firms may invest in non-specific training if others do the same, because they would otherwise suffer a competitive disadvantage or need to pay high wages in order to attract trained workers. Government intervention can be socially desirable to turn training into a focal equilibrium.
Keywords: L43; L92; D42; L22; 330; General training; human capital; oligopoly; turnover; Betriebliche Bildungsarbeit; Bildungsinvestition; Wettbewerb; Oligopol; Lohn; Arbeitsmobilität; Spieltheorie; Theorie